Participatory planting and management of indigenous trees: lessons from Chivi district, Zimbabwe - Gerhardt, K.; Nemarundwe, N. (2006)
This paper reports on action research that evaluated local perceptions and knowledge of indigenous tree planting and management in the Romwe catchment, Chivi district, southern of Zimbabwe. The species tested were the overexploited Afzelia quanzensis, important for timber and carvings of sculptures and utenssils; Sclerocarya birrea, the marula tree used for wood, bark, and fruit; and Brachystegia glaucescens, the dominant miombo tree species, used for firewood, fiber, and fodder. Participants volunteered to plant and manage the test seeds, while a research team monitored their activities and results for 26 months. For Afzelia quanzensis, the germination rate was 81% and 69% of the seedlings were still alive after one year. In the case of Sclerocarya birrea, the germination rate was 69%, and the one-year survival rate was 50%. For Brachystegia glaucescens, the germination rate was only 30%, and the survival rate was 31%. The main reasons for planting were to provide shade, to serve as a windbreak, and to conserve and gain individual control over dwindling natural resources, particularly Afzelia quanzensis. Women were generally more active and innovative than men. For intance, they searched for their own seeds or seedlings in the bush when there weren't sufficient plants. Some participants tried out various methods of pest and disease control, water conservation, and moisture retention. Group feedback sessions and informal interactions provided the opportunity to share experiences. The participants learned that indigenous trees can be purposefully planted and were not simply a gift from God. Despite the droughts and political instability of recent years, a growing number of people became involved in tree planting during 2002-2003. As a result, there is now greater awareness among the local population of dwindling resources and their future potential.